Analysis of Rice Field Drought Level in Pemalang Regency 2019 – 2021 - Indah Purwati; Arie Yulfa (Universitas Negeri Semarang, 2022)
Pemalang is a district that has rice fields up to 36 thousand hectares and becomes a buffer area for rice commodity in Central Java and becomes a focus in maintaining availability and food reserves. However, Pemalang Regency is vulnerable to the threat of drought that often hits the Central Java region. Therefore, information is needed about rice field drought as a form of mitigation and supporting food security by the sustainable development goals (SDGs). The purpose of this research is to determine the level of rice fields' drought in the rainy and dry seasons from 2019 to 2021 and displays in the form of web gis that all circles can access. The data needed in this study include normalized difference vegetation index (NDVI) map, normalized difference water index (NDWI) map, land surface temperature (LST) map, hydrogeology map, land type map, and rice field map. The result of this study is the formation of a map of the drought level of rice fields in the Pemalang Regency divided into five classes, namely very low, low, medium, high, and very high. Ulujami and Belik are the sub-districts with the broadest moderate drought rate from the data processing. Then Ulujami, Watukumpul, and Belik are districts with the broadest area of high drought, and Randudongkal is a subdistrict with the broadest very high drought area.